Lower limb cellulitis in non-diabetic patients: a prospective study - Adimoolam, Eakanathan; Pitchai, Rajapandi (International Surgery Journal, 2018)
Background: Lower limbs are commonly involved in cellulitis as they are more susceptible to injuries. This study analyzes the various causes and risk factors for cellulitis in the non-diabetics. Methods: This prospective study was conducted at the Department of General Surgery, Government Thanjavur Medical College and included 100 non-diabetic patients with lower limb cellulitis. The severity of cellulitis was graded as per the CREST guidelines. Demographics, risk factors, grades, management and treatment outcomes were recorded and analyzed. Results: Cellulitis was more common in females (58%) and old age group (37%). It was more unilateral (86%) and resulted more from post bite wounds (21%). 76% had culture-positive wound infections. Severe grades of cellulitis needed surgical intervention and many patients needed skin grafting. Conclusions: Nondiabetic patients with lower limb cellulitis can also result in severe morbid consequences but in the absence of co-morbid illness, they usually recover with minimal residual disabilities. Nondiabetic elderly patients have to be motivated to take care of their feet as the diabetic patients, as neglect of minor trauma or bites can lead to morbid illness necessitating major treatment like skin grafting.